Learning to Write Negotiation Texts as Part of the High School Independent Curriculum - Putra Abda’u, Muhammad Fishal; Setiawan, Arif; Musaffak, Musaffak (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to describe the learning outcomes of writing negotiation texts by X E1 class students of SMAN 1 Bangsri in accordance with the Merdeka Curriculum in X E1 class X E 1 class. This study is qualitative in nature. This study employs a case study methodology. This study utilized student worksheets, learning modules, and literature source texts as its data and data sources. Various data collection methods include observations, interviews, and documentation. Triangulation models are employed for data analysis. This study's findings are the preparation of learning to write negotiation texts in X E1 class of SMAN 1 Bangsri, based on an autonomous curriculum that has been implemented effectively in accordance with the most recent curriculum guidelines. The creation of instructional modules is associated with the independent curriculum system. The teacher's instructional module conforms to the requirements of the independent curriculum. Currently, the implementation of learning employs an independent curriculum whose primary objective is to encourage students to develop their potential. The learning process emphasizes students' exploration of their surroundings. The results of students' ability to write negotiation texts are evident in four areas: content, structure, linguistic norms, and effective sentence construction. Content-wise, 83% of X E1 class students in SMAN 1 Bangsri are categorized as having adequate skills. Furthermore, the ability of X E1 class students of SMAN 1 Bangsri from the perspective of completeness of structure, which is 100%, is categorized as excellent. The ability of X E1 class students of SMAN 1 Bangsri from the perspective of language elements, which is 64%, is categorized as quite good. Therefore, the aggregate average score across all subject areas was 86%, and 14% of students did not satisfy the KKM. Based on this, 86 % comes within the category of excellent. Thus, the X E1 class students' learning of composing negotiation texts produced positive results.